2014
DOI: 10.3109/0886022x.2014.949765
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trimetazidine on the Akt/eNOS signaling pathway and oxidative stress in anin vivorat model of renal ischemia-reperfusion

Abstract: Renal ischemia reperfusion (I/R) injury, which occurs during renal surgery or transplantation, is the major cause of acute renal failure. Trimetazidine (TMZ), an anti-ischemic drug, protects kidney against the deleterious effects of I/R. However its protective mechanism remains unclear. The aim of this study is to examine the relevance of Akt, endothelial nitric oxide synthase (eNOS), and hypoxia inducible factor-1a (HIF-1a) on TMZ induced protection of kidneys against I/R injury. Wistar rats were subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 37 publications
5
26
0
5
Order By: Relevance
“…In the present experiment, we demonstrated that SFI increased eNOS phosphorylation and NO production by enhancing Akt phosphorylation, which is agreement with the report from Wang et al, who showed that ginsenoside Rg3, a main component of SFI, mediated a cardioprotective effect against MIRI-induced apoptosis via Akt/eNOS signaling. 41) Trimetazidine is a piperazine-derived agent with protective effects that is effective in the treatment of myocardial, renal and liver ischemia/reperfusion injury in which the Akt/eNOS signaling pathway is involved. 42) The results of the present study are similar to those reported in an in vivo rat model of IR.…”
Section: Discussionmentioning
confidence: 99%
“…In the present experiment, we demonstrated that SFI increased eNOS phosphorylation and NO production by enhancing Akt phosphorylation, which is agreement with the report from Wang et al, who showed that ginsenoside Rg3, a main component of SFI, mediated a cardioprotective effect against MIRI-induced apoptosis via Akt/eNOS signaling. 41) Trimetazidine is a piperazine-derived agent with protective effects that is effective in the treatment of myocardial, renal and liver ischemia/reperfusion injury in which the Akt/eNOS signaling pathway is involved. 42) The results of the present study are similar to those reported in an in vivo rat model of IR.…”
Section: Discussionmentioning
confidence: 99%
“…A deficiency of eNOS-derived NO exacerbates the early stage of non-alcoholic steatohepatitis pathogenesis in a mouse model via the regulation of hepatic tissue blood flow [27]. eNOS is important in the progress of neovasculogenesis [28] and participates in various disorders by various signaling pathways [2931]. eNOS plays a central role in the maintenance of endothelial homeostasis [32].…”
Section: Discussionmentioning
confidence: 99%
“…Ряд экспериментальных и клинических исследований позволяют предполагать наличие у триметазидина нефро-протективного эффекта [78][79][80][81][82]. Например, при назначе-нии триметазидина МВ за 2 дня до проведения инвазив-ных коронарных процедур (коронарография и др.)…”
Section: на сегодняшний день обсуждаются плейотропные эффекты триметаunclassified